KUALITAS AIR SUNGAI MUSI - Iis Ambarwati; I Gede Sugiyanta; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2013)
This research is one of description research that have purpose to describe about The Quality of Musi River’s Water in 1 Ulu Village Sberang Ulu 1 Subdistrict Palembang 2012. Point of view in this research is consist of two aspects that is chemical and physic aspect. The physic aspects consist of turbidity, temperature, and water colour. Whereas, for the chemical aspects consist of Nitrat, Nitrit, H2S, and COD. The object of this research all of Musi River unite from upper course to downstream to flash past in 1 Ulu Village. The technics to take sample that used into this research is purposive sample with used three areas sample and each of one area are consist of one to two observation point. The technics of data processing was did with laboratory test, survey object, observation, documentation, and interview. The data analysis processing used to analysis the result of research by three areas that is the exploration description. The result showed that the water quality Musi River polluted. It is evident from the results of the test parameters have exceded water quality standards for rivers in South Sumatera Governor Regulation No. 16 Years 2005. Key words: The quality of water, Musi River